Novel optimized biopolymer-based nanoparticles for nose-to-brain delivery in the treatment of depressive diseases. Issue 48 (4th August 2020) - Sorrentino, Alessandro; Cataldo, Antonino; Curatolo, Riccardo; Tagliatesta, Pietro; Mosca, Luciana; Bellucci, Stefano
Abstract : A valid option to bypass the obstacle represented by the blood–brain barrier (BBB) in brain delivery is the use of the unconventional intranasal route of administration. Abstract : A valid option to bypass the obstacle represented by the blood–brain barrier (BBB) in brain delivery is the use of the unconventional intranasal route of administration. The treatment of depressive diseases, resulting from the depletion of a neurotransmitter in the inter-synaptic space, such as serotonin, is indirectly treated using molecules that can permeate the BBB unlike the latter. In the present article, a set of nanovectors were produced using a mucoadhesive biopolymer, i.e. alginate (Alg). Optimizing the reaction, polymeric nanoparticles having diameter of 30–70 nm were produced, and water stable multi-walled carbon nanotubes functionalized (MWCNT-COOH)/Alg complexes were obtained. These nanovectors were loaded with serotonin, evaluating drug loading/release. By means of Raman microscopy, the cellular internalization of the (MWCNT-COOH)/Alg complex was demonstrated. A complete biocompatibility on neuronal cells was proved for the whole set of nanovectors. Finally, a method of self-administration was tested, which involves the use of a household apparatus, such as an aerosol machine, observing a fine particulate, able to deliver the nanovectors through the nose.